Margaret Truman's Experiment in murder : a capital crimes novel - Bain, Donald, 1935-2017 (Truman, Margaret, 1924-2008. Capital crimes novel., 2012)
When a Washington psychiatrist is found dead in his office, Mackenzie Smith is called in to defend one of his patients who has become a suspect. Then information emerges that links the slain shrink to a highly secret CIA mind control project. A programmed assassin strikes and kills the wildly popular frontrunner in the presidential race. As a result of the assassination, the other government agencies have become aware of the rogue CIA program. They want to infiltrate it, and Mac Smith's client, the accused killer, seems to be their perfect spy. But the assassin is programmed to kill anyone who threatens him or his organization, which includes Mac and his wife, Annabel.